Design and analysis of wavelength division multiplexed passive optical network for FTTx application / Mohd Syukri Mohd Hashim - Mohd Hashim, Mohd Syukri (2012)
The steady increase in the bandwidth demand for broadband services has increased the volume of generated traffic in our communication networks. Moreover, a further growth in the number of people that need broadband access is forecasted. Legacy copper based networks are incapable to meet this future bandwidth demands and therefore have motivated the need to implement next generation networks. To answer this is with optical networks and a promising technology for these networks is Wavelength Division Multiplex Passive Optical Network (WDM-PON). This project aims to describe the theories, design, and analysis of a WDM-PON access network based on FTTx application simulated in OptiSystem 7.0. The theoretical part of this project is to study in depth on access networks between Active Offtical Network (AON) and Passive Optical Network (PON) and decide which the most optimal option to be implemented. Next, the study will looking into the definition of FTTx networks and its configurations, moving to elaborate about the operating principles of WDM-PON and explanation on device required in the system. The design part was carried out by analyzing the transmitter first either directly-modulated which used WDM transmitter (Txl) or external-modulated transmitter (Tx2). Tx2 consists of CW Laser, NRZ Pulse Generator, Pseudo-Random Bit Sequence Generator (PRBS), and Mach-Zehnder Modulator (MZM). Finally, the analysis part is to find the maximum length and suitable bit rate in WDM-PON design with up to 8 numbers end user. This is done by observing the quality and performance of signal in subscriber Optical Network Unit (ONU) in terms of eye diagram, Bit-Error Rate (BER), Q factor, and total power. At the end of the project, the performance shows that the maximum bit rate that the system can support is 2.5Gbps whereas for the maximum distance is 18km with 8 numbers of user.